Hyper-connectivity of the Thalamus in during Early Stages following Mild Traumatic Brain Injury - Sours, Chandler (Brain Imaging Behav, 2015)
The thalamo-cortical resting state functional connectivity of 7 sub-thalamic regions were examined in a prospectively recruited population of 77 acute mild TBI (mTBI) patients within the first 10 days (mean 6±3 days) of injury and 35 neurologically intact control subjects using the Oxford thalamic connectivity atlas. Neuropsychological assessments were conducted using the Automated Neuropsychological Assessment Metrics (ANAM). A subset of participants received a magentic resonance spectroscopy (MRS) exam to determine metabolite concentrations in the thalamus and posterior cingulate cortex. Results show that patients performed worse than the control group on various subtests of ANAM and the weighted throughput score, suggesting reduced cognitive performance at this early stage of injury. Both voxel and region of interest based analysis of the resting state fMRI data demonstrated that acute mTBI patients have increased functional connectivity between the various sub-thalamic regions and cortical regions associated with sensory processing and the default mode network (DMN). In addition, a significant reduction in NAA/Cr was observed in the thalamus in the mTBI patients. Furthermore, an increase in Cho/Cr ratio specific to mTBI patients with self-reported sensory symptoms was observed compared to those without self-reported sensory symptoms. These results provide novel insights into the neural mechanisms of the brain state related to internal rumination and arousal, which have implications for new interventions for mTBI patients with persistent symptoms. Furthermore, an understanding of heightened sensitivity to sensory related inputs during early stages of injury may facilitate enhanced prediction of safe return to work.